Pengembangan Sistem Monitoring Mengidentifikasi Vital Sign Suhu Tubuh dan Jantung pada Orang Tua - Rezka Aditya Nugraha Hasan; Fajar Pradana; Fitra Abdurrachman Bachtiar (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
Vital sign checks in today's technology can be implemented anywhere, such as at home, in hospitals, and outdoors (while traveling). The proposed vital signs monitoring system can assist clinicians by delineating traces of critical physiological parameters, generating early warnings/warnings and indicating any significant changes to the data. The monitoring system developed has the advantage of being able to wirelessly interconnect between sick patients and their families at home. The development carried out is to make a monitoring system capable of taking readings from the body and heart temperatures of the patients being examined and providing early warnings if the parameters that are read are abnormal. The system is able to send data from the reading of the two aspects to the data processing center. In the data processing center, the system will analyze the patient's condition based on the patient's temperature and heart rate. And from the results of the study, it was found that the system that has been built can measure the patient's body temperature and heart rate according to the selected sensor port and the system can store patient data. The system is able to communicate well where the sensor readings can be displayed on the GUI system according to the pre-set port and identify the patient's condition by comparing the patient's body temperature and heart rate data with normal human conditions.